CROP DIVERSIFICATION IS ONE OF THE REFERENTIAL PATTERNS FOR ENHANCED CROP PRODUCTION: A SECONDARY STUDY ON PURBA & PASCHIM MEDINIPUR DISTRICT IN WEST BENGAL - Jana, Kajalbaran (International Journal of Research -GRANTHAALAYAH, 2021)
Crop diversification is a planned innovative approach to maximize land usage with optimum crop production to aim at minimizes losses of seasonal and other impacts on crop. India being one of the biggest countries of agricultural economy and West Bengal, although tiny in size, is one of the biggest producers of few agricultural produces like rice, potato, oil seed etc. Within West Bengal, undivided retained a significant role in agricultural produce. After division of the district in to & during 2000, most of the cultivable land is within . has some pocket areas that has good reputation of cultivation. The Crop diversification is the need for the hour for small cultivable area. In this particular scenario, this study has tried to focus on the state of crop diversification in the district with a comparative study on district because of its history of its erstwhile geographical tie up. At the same time, it has also attempted to find out the effect of crop diversification on crop production. In this particular aspect this study has focused on the condition of this particular aspect on undivided district also. It has found that crop diversification on the basis of principal food crop in district has significantly positive relationship with production but has insignificant negative relationship in between crop diversity of rice with its production. In undivided there has been positive relationship between crop diversity and crop production in both principal food crops and rice. This has attracted to conclusive remark that division of district has impaired the scope of crop diversification of district but it has sufficient space to improve it as the relationship has indicated positive direction to that end although negative direction in rice crop would be matter further research.